Penguatan Perilaku Hidup Bersih dan Sehat melalui Sosialisasi Interaktif pada Siswa Sekolah Dasar di Desa Babakan Asem - Nurhikmah, Dentian; Intani, Adela Nur; Arista, Gina Dwi; Lestari, Aprilia Kasih (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Perilaku Hidup Bersih dan Sehat (PHBS) is an important indicator in improving public health, especially for elementary school-aged children who are in the phase of forming long-term habits. Students' low knowledge of basic health practices, especially in rural areas, is an obstacle to optimal PHBS implementation. This community service activity aims to increase students' knowledge, understanding, and awareness of PHBS through educational outreach at Babakan Asem Elementary School and Neglasari Elementary School. The outreach method used a multimodal learning approach that included interactive lectures, visualizations through PowerPoint and video media, discussions, icebreakers, demonstrations of the seven steps of handwashing, and the "Fill My Plate" group activity. The results of the activity showed an increase in students' knowledge and abilities, students were able to understand and repeat the material presented. Student enthusiasm and school support indicated that the outreach was effective. This activity is a relevant preventive strategy in supporting public health development and preventing health problems related to hygiene and nutrition in children.